Between context and comparability: Exploring new solutions for a familiar methodological challenge in qualitative comparative research. (17th February 2020) - Kosmützky, Anna; Nokkala, Terhi; Diogo, Sara
Abstract: Finding the balance between adequately describing the uniqueness of the context of studied phenomena and maintaining sufficient common ground for comparability and analytical generalisation has widely been recognised as a key challenge in international comparative research. Methodological reflections on how to adequately cover context and comparability have extensively been discussed for quantitative survey or secondary data research. In addition, most recently, promising methodological considerations for qualitative comparative research have been suggested in comparative fields related to higher education. The article's aim is to connect this discussion to comparative higher education research. Thus, the article discusses recent advancements in the methodology of qualitative international comparative research, connects them to older analytical methods that have been used within the field in the 1960s and 1970s, and demonstrates their analytical value based on their application to a qualitative small‐N case study on research groups in diverse organisational contexts in three country contexts. Abstract: Die Balance zwischen der adäquaten Beschreibung der Besonderheiten von Untersuchungsfällen, und der Herstellung einer hinreichenden Basis für Vergleichbarkeit und analytische Verallgemeinerung zu finden, wird in der Diskussion zu Vergleichsmethodologie als eine zentrale Herausforderung angesehen. Methodologische Überlegungen dazu, wie die Besonderheiten von Fällen und Vergleichbarkeit in Studien gleichermaßen adäquat gefasst werden können, wurden für die quantitative Forschung bereits ausführlich diskutiert. In jüngster Zeit wurden zudem vielversprechende methodische Überlegungen für die qualitativ vergleichende Forschung in komparativen Forschungsfeldern, die zur Hochschulforschung benachbart sind, gemacht. Der Artikel will diese Diskussion in die vergleichende Hochschulforschung einführen. Er diskutiert daher neuere methodologische Vorschläge in der qualitativen, international vergleichenden Forschung, stellt eine Verbindung zu älteren analytischen Ansätzen her, die in der Hochschulforschung in den 1960er und 1970er Jahren zum Einsatz kamen, und demonstriert den analytischen Wert dieser Vorschläge anhand einer qualitativen Fallstudie zu Forschungsgruppen in unterschiedlichen Organisationskontexten in drei verschiedenen Länderkontexten.